Use of liver graft with Schistosoma mansoni: report of an unexpected finding - Fonseca Neto, Olival Cirilo Lucena da (2019)
The increasing amount of transplants performed along with the use of marginal donor grafts have led to the identification of infectious agents, such as Schistosoma mansoni, in asymptomatic donor grafts which had not yet been diagnosed before being transplanted. Thus, the present study aims to describe the case report of a patient who received a livergraft with Schistosoma mansoni, not compromising the result of liver transplantation in the mediate postoperativeperiod.